(untitled) (International Journal of Environmental Sciences, 2025)
This paper investigates how economic conditions moderate the association of audit committee characteristics and audit quality with stock prices for UK manufacturing companies. This paper uses a quantitative research approach for analysis of financial data from 20 UK manufacturing firms over the years 2014-2023. The data has been collected from annual reports and refinitive. The study employs panel data GLS regression to evaluate how stock price movements in response to audit committee attributes and audit quality change in reaction to GDP growth. The study indicated that audit committee size and independence have insignificant impact on the stock market performance. However, higher audit quality negatively impact on the stock returns. GDP growth positively moderates the relationship between audit committee independence and stock performance, while it has insignificant impact on audit committee size or quality.